Mapping Cannabis Social Clubs in Europe - Pardal, Mafalda (European journal of criminology, 2022)
Cannabis Social Clubs (CSCs) are typically non-profit associations of adult cannabis users who collectively produce and distribute cannabis among themselves. Since the emergence of the model in Spain during the 1990s, other countries may have seen the appearance of CSCs (or CSC-like associations) but there is a dearth of knowledge about the phenomenon in Europe. The goals of this analysis are to: (1) map the presence of CSCs across the European Union; and (2) examine how CSCs are operating in such settings. The data included in our analysis derive from a 2018?19 survey. The 30-item questionnaire comprised questions about CSCs? origins and relations with other stakeholders and organizations, the types of activities the CSCs developed and their views on cannabis regulation. The questionnaire was translated into all the official languages of the EU zone and sent via email to the participants. In total, 81 CSCs completed the questionnaire. Beyond Spain and Belgium, where the CSC presence has already been documented, we were able to identify CSCs in 11 other countries. The longest-running CSC in our sample was established in 1999, but most emerged in the past decade. The smallest CSC in our sample reported six registered members, whereas the largest counted a total of 5000 members. Most CSCs were cultivating or distributing cannabis to their members at the time of the survey, but engaged in other informative, entertainment and activist activities as well. The CSC model remains prohibited across the EU. CSC activists have thus by and large shaped the way CSCs operate, often adapting to domestic law particularities or law enforcement activities. In this article, we present and discuss the range of CSC practices from 13 different European countries, and what these represent for the consideration of the CSC model in current policy debates.